On Transcendental Instance: Between History and Absence of History - Catucci, Stefano (Aesthetica Preprint, 2022)
Drawing on what Emilio Garroni claims in the essay Spazialità with regard to the relationship between spatiality and temporality, the present contribution intends to reflect on the way in which he investigated the constitutively paradoxical nature of the transcendental instance, whose sense, as a condition a priori, is subtracted from historical becoming despite the fact that it is structurally implicated in it. Through a comparison with the notion of the ‘aggregate’ and with the Foucauldian concept of the historical a priori, the essay will attempt to demonstrate that for Garroni, spatiality and temporality, the consolidation of a need for systematicity and the historicisation of a need for processuality, are not only compatible but, strictly speaking, are not even separable.